A reply to Páll-Gergely’s suggestions to improve the taxonomy index (T-Index) introduced by Valdecasas (2011) - Valdecasas, Antonio G. (Zootaxa, 2014)
In a letter to Nature, Valdecasas et al. (2000) criticised the Impact Factor (IF) which calculates the number of citations in scientific publications, particularly within biodiversity studies. Subsequently, even though Krell (2000, 2002) claimed that IF was not relevant to taxonomy, however, IF has continued to play and increasingly important role in evaluations of scientists, taxonomists not excepted (Meier & Lim, 2009).